Work and non-work dichotomy: The influence of inter-role conflict on quality of life of managers in Klang Valley, Malaysia - Ismail, Izhairi (The Journal of Global Business Management, 2006)
The focus of the current study is to evaluate the associations between both work and non-work domain variables and inter-role conflict. Specifically; the work domain variables such as, work role conflict, work role ambiguity and work time commitment and the non-work domain variables; such as family conflict, family time commitment and leisure involvement were expected to influence the degree of inter-role conflict. Inter-role conflict, in turn was explored in relations to quality of life. The spillover theory provided justifications for most of the connections among variables in this study. Questionnaire surveys were self-administered to a sample of three hundred and fifty male and female managers living and working in the city of Kuala Lumpur and in the area Klang Valley, Malaysia. The managers were married and had at least one child living in the same home. Descriptive results and correlations were analysed using SPSS (Version 11) and Path Analysis was conducted using LISREL 8.52 (Jöreskog & Sörbom, 2002). Findings revealed that work role ambiguity, leisure involvement and family time commitment were significantly related to inter-role conflict. Contradictory to expectations, work role conflict and family conflict were negatively and significantly affiliated with inter-role conflict. The same connection involving work time commitment was not significant. As anticipated, inter-role conflict was negatively and significantly related to quality of life.